Penerapan Terapi Pijat Refleksi Untuk Mengurangi Rasa Nyeri Pada Ibu Post Sectio Caesarea H-O Di Ruang Anggrek (Nifas) RSUD. Dr T.C Hillers Maumere. - Faridah Derang; Regina Ona Adesta (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
With a scar from a caesarean section operation sectio caesarea cause pain to the patient so the patient tends to just lie down, therefore postpartum mothers with a history sectio caesarea early mobilization care is needed. On mother sectio caesarea allowed to get out of bed no later than 24-48 hours after giving birth. one way to reduce pain in mothers after surgery sectio caesarea is by doing reflexology massage therapy. The purpose of this case study is to find out adaptation of pain levels in post-mothers sectio caesarea after reflexology massage therapy. The method used in this case study case study design with a nursing care process approach. The subjects in this case study were 2 patients, obtained from inclusion and exclusion criteria, data collection using Numerik rating scale (NRS). The case study results show that on average pain level of the two patients after being given therapeutic intervention reflexology massage for 2x8 hours, namely experiencing changes from severe pain to moderate pain and the patient looks more comfortable and relaxed. The conclusion of this case study shows that there are changes that occur after it is given reflexology therapy intervention for the two patients and experienced a decrease in the pain scale so that both patients are able to adapt to the pain what they feel.